Gut Microbiota-Related Evidence Provides New Insights Into the Association Between Activating Transcription Factor 4 and Development of Salt-Induced Hypertension in Mice - Liu, Tian-hao; Tao, Wen-cong; Liang, Qiu-er; Tu, Wan-qing; Xiao, Ya; Chen, Li-guo (Frontiers in Cell and Developmental Biology, 2020)
Activating transcription factor 4 (ATF4), which regulates genes associated with endoplasmic reticulum stress, apoptosis, autophagy, the gut microbiome, and metabolism, has been implicated in many diseases. However, its mechanistic role in hypertension remains unclear. In the present study, we investigated its role in salt-sensitive hypertensive mice. Wild-type (WT) C57BL/6J mice were used to establish Atf4 knockout (KO) and overexpression mice using CRISPR-Cas9 and lentiviral overexpression vectors. Then, fecal microbiota transplantation from Atf4+/− mice and vitamin K2 (VK2) supplementation were separately carried out in high-salt-diet (8% NaCl)-induced mice for 4 weeks. We found that Atf4 knockout inhibited and Atf4 overexpression enhanced the increase in blood pressure and endothelial dysfunction induced by high salt intake in mice, while regulating the gut microbiota composition and VK2 expression. It was further verified that ATF4 is involved in the regulation of salt-sensitive hypertension and vascular endothelial function, which is achieved through association with gut microbiota and may be related to VK2 and different bacteria such as Dubosiella. In addition, we found that VK2 supplementation prevents the development of salt-sensitive hypertension and maintains vascular endothelial function; moreover, VK2 supplementation increases the abundance of intestinal Dubosiella and downregulates the relative expression of Atf4 in the thoracic aorta of mice. We conclude that ATF4 plays an important role in regulating gut microbiota and VK2 production, providing new insights into the association between ATF4 and development of salt-induced hypertension in mice, meanwhile contributing to the development for a new preventive strategy of hypertension.